2021
DOI: 10.1183/13993003.03229-2020
|View full text |Cite
|
Sign up to set email alerts
|

The risk of community-acquired pneumonia in children using gastric acid suppressants

Abstract: With the increased use of acid suppressants, significant potential complications, such as community-acquired pneumonia are becoming more apparent. Paradoxically, in spite of an increased focus on potential complications, there is an increased use of acid suppressants in children and a lack of data specifically targeting the association between acid suppressants and community-acquired pneumonia. Our main objective was to evaluate the risk of community-acquired pneumonia in children using acid suppressants (prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…Furthermore, recent evidence,7 8 especially a large-scale randomised controlled trial8 did not find a significant difference in risk of pneumonia between patients randomised to pantoprazole and placebo. Given the scarcity of previous data in children,9 10 our study substantially expands on the understanding of this drug safety concern in the paediatric population.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Furthermore, recent evidence,7 8 especially a large-scale randomised controlled trial8 did not find a significant difference in risk of pneumonia between patients randomised to pantoprazole and placebo. Given the scarcity of previous data in children,9 10 our study substantially expands on the understanding of this drug safety concern in the paediatric population.…”
Section: Discussionmentioning
confidence: 98%
“…In children, only two population-based studies9 10 have examined this drug safety issue. A recent cohort study10 observed a twofold increased risk of pneumonia within the first 30 days of current use of PPIs, as compared with non-use, whereas a nested case–control study found a neutral association when comparing current PPI use to past use 9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the past two decades, accumulating evidence indicates increased risks of pneumonia under the use of PPIs [7,8,20], whereas others failed to show such associations [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…These agents increase gastric pH, which in turn leads to increased survival and growth of microbes in the stomach. 17 Several studies in both adults and children 18,19 have suggested that the use of gastric acid suppression therapy increases the risk of respiratory infections, although the topic is controversial due to a lack of controlled trials.…”
Section: Pathophysiology and Risk Factorsmentioning
confidence: 99%